Oil prices and stock returns: Evidence from emerging markets - Manukyan, Kristina (My University, 2013)
This thesis analyzes relationships between oil price risk and 23 emerging market stock returns starting from the middle of February 2006 until the end of April 2012. The study is done from the standpoint of a Euro Zone investor or an international investor who has a Euro trading account. There is a lot of financial researches investigating mentioned dependency, however only few is focused on emerging market economies. The purpose of this study is to contribute to literature analyzing oil price risk and emerging stock market returns by examining further work started by Bacher and Sadorsky (2006). Conditional and unconditional multifactor model is used including following factors: oil price risk, world market risk and oil exchange risk. Oil price movement and global financial crisis risk factor are also included into research using dummy variables. Both conditional and unconditional multifactor model show oil price risk has a major impact on the emerging stock market returns, however only in case the country in question is a big oil consumer. Significant and high world market betas are found contributing to the positive tradeoff expectation between risk and returns. In 80% of analyzed cases oil exchange rate risk shown to be one of the important drivers of excess stock market returns in emerging economies. There was the evidence found of either weak negative or no effect of the global financial crisis on the emerging stock market returns. Though the outcome is consistent with previously done studies, author of this thesis attributes it to limitations established in the current research paper (such as selected time range for analysis and the generalization of the crisis timeline for all the countries under study).
Keywords: Oil price risk; crisis risk; stock returns; emerging stock markets; multifactor model.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|